Development of BaO–ZnO–B2O3glasses as a radiation shielding material - N. Chanthima (2018)
© 2016 Elsevier Ltd The effects of the BaO on the optical, physical and radiation shielding properties of the xBaO: 20ZnO: (80−x)B 2 O 3 , where x=5, 10, 15, 20 and 25 mol%, were investigated. The glasses were developed by the conventional melt-quenching technique at 1400 °C with high purity chemicals of H 3 BO 3 , ZnO, and BaSO 4 . The optical transparency of the glasses indicated that the glasses samples were high, as observed by visual inspections. The mass attenuation coefficients (µ m ), the effective atomic numbers (Z eff ), and the effective electron densities (N e ) were increased with the increase of BaO concentrations, and the decrease of gamma-ray energy. The developed glass samples were investigated and compared with the shielding concretes and glasses in terms of half value layer (HVL). The overall results demonstrated that the developed glasses had good shielding properties, and highly practical potentials in the environmental friendly radiation shielding materials without an additional of Pb.